Bilingualism and Attention in Typically Developing Children and Children With Developmental Language Disorder - Park J.; Miller C.; Sanjeevan T.; van Hell J.; Weiss D.; Mainela-Arnold E. (NLM (Medline), 2022)
Purpose: The aim of the current study was to investigate whether dual language experience modulates the efficiency of the 3 attentional networks (alerting, orienting, and executive control) in typically developing (TD) children and in children with developmental language disorder (DLD).
Method: We examined the attentional networks in monolingual and bilingual school-aged children (ages 8–12 years) with and without DLD. TD children (35 monolinguals, 23 bilinguals) and children with DLD (17 monolinguals, 9 bilinguals) completed the Attention Network Test (Fan et al., 2002; Fan, McCandliss, Fossella, Flombaum, & Posner, 2005).
Results: Children with DLD exhibited poorer executive control than TD children, but executive control was not modified by bilingual experience. The bilingual group with DLD and both TD groups exhibited an orienting effect, but the monolingual group with DLD did not. No group differences were found for alerting.
Conclusions: Children with DLD have weak executive control skills. These skills are minimally influenced by dual language experience, at least in this age range. A potential bilingual advantage in orienting may be present in the DLD group.